2017
DOI: 10.1007/s40864-017-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Aspects of Wheel–Rail Contact: A Review of Wear Mechanisms and Effective Factors on Rolling Contact Fatigue

Abstract: Nowadays, the railway is considered as a means of fast, aggregate and secure transportation. The issue of the rail and wheel contact is one of the most fundamental aspects in the railway system since inappropriate interactions create problems such as wear and a negative effect in the dynamic functioning of the train. In this research, we analyze one of the most important phenomenon in a railway system which is the contact of the rail and wheel. This review is done in the scope of the most fundamental deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The profile of the rail gauge corner and the wheel flange surface are not flat. Their shapes are designed to reduce the friction between them [26]. Therefore, the surface of the wheel flange front side to be detected by the sensor is convex and its factor on the sensing area is 0.25.…”
Section: The Inductive Sensor-based Measurement Method Mechanics Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile of the rail gauge corner and the wheel flange surface are not flat. Their shapes are designed to reduce the friction between them [26]. Therefore, the surface of the wheel flange front side to be detected by the sensor is convex and its factor on the sensing area is 0.25.…”
Section: The Inductive Sensor-based Measurement Method Mechanics Andmentioning
confidence: 99%
“…This method has different disadvantages: need of calibration, dependence on the skills of the operator, low accuracy and precision, and the need to stop the vehicle operations for measurement purpose in depots or workshop. The wheel flange wear measurement methods have been improved [26] as a result of advancement of technology in railway systems all over the world. A portable electronic gauge [27] can measure the wheel rim diameter, wheel flange thickness and height, when the train is in the workshop, using simple operation.…”
Section: Wheel Flange Wear Measurement Techniquesmentioning
confidence: 99%
“…In previous studies [1, 2, 4-8, 12, 15, 16], it has been revealed that rail wear depends greatly on vehicle speed. Influences of superelevation on rail wear have been previously emphasized [2,3,5,12]. Taking into account the findings obtained from previous studies, traffic load, track curvature, superelevation, and train speed were selected as explanatory variables for the rail wear models proposed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The material loss which occurs on the contact surface of the rail and wheel is called wear [1]. Wear mechanisms include abrasive wear, adhesive wear, delamination wear, tribochemical wear, fretting wear, surface fatigue wear, and impact wear [2]. Significant changes take place in the rail profile as a result of wear [1].…”
Section: Introductionmentioning
confidence: 99%
“…Wear (especially at the wheel tread and rail ball interface under straight-line running conditions, as studied in this paper and shown in Figure 1) will directly lead to the reduction of rail height, thus causing plastic deformation of materials and failure of surface materials [4]. Common wear mechanisms include abrasive wear, adhesive wear, delamination wear [5]. Fatigue derives from the formation of cracks and the detachment of material from the surface due to the repetitive application of alternating forces [6,7], which by first causing defects or surface cracks, may eventually destroy some components [8].…”
Section: Introductionmentioning
confidence: 99%